MENOPAUSAL HORMONE THERAPY WITH DYDROGESTERONE: ASPECTS OF EFFICACY AND SAFETY OF ULTRA-LOW DOSES - A. A. Smetnik (Медицинский совет, 2017)
A number of studies have shown that menopausal hormone therapy (MHT), consisting of 1 mg 17ß-estradiol and 5 mg dydrogesterone, is effective to reduce the severity of menopausal symptoms and increases bone mineral density in postmenopausal women [1] and at the same time has a favorable safety indicators for the endometrium and the pattern of bleeding [2, 3]. Nevertheless, current guidelines recommend the use for the treatment of menopausal symptoms of the lowest effective dose of estrogen [4–6]. In this regard, we developed a new combined mode of MHT with continuous use of ultra-low doses of hormones – 0.5 mg 17ß-estradiol and 2.5 mg of dydrogesterone. The use of ultra-low doses of estrogen protects the endometrium by lower doses of progestogen. Similar combinations of low doses of MHT can reduce the incidence of adverse events, such as the sensitivity of the mammary glands, uterine bleeding, cardiovascular disease, ischemic stroke and venous thromboembolic complications, and at the same time, to maintain effectiveness against menopausal symptoms [7–11]. The appearance of in the arsenal of gynecologists of ultra-low dose MHT is likely to improve the patient’s adherence to this treatment regime. In addition, a low dose of estrogen is particularly useful for older women (>59 years).